2018
DOI: 10.3390/molecules23102668
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Bergenin against Cyclophosphamide-Induced Immunosuppression by Immunomodulatory Effect and Antioxidation in Balb/c Mice

Abstract: In this study, the aim was to investigate the effect of bergenin on immune function and antioxidation in cyclophosphamide (Cy)-induced immunosuppressed mice. Firstly, we estimated its effect on immune organs. Histological analysis and indexes of immune organs showed that cyclophosphamide exhibited spleen and thymus injury compared with the normal control, which was alleviated by bergenin. Secondly, bergenin also enhanced the humoral immune function through increasing the level of IgM and IgG in serum. Thirdly,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 47 publications
(58 reference statements)
5
36
0
Order By: Relevance
“…TCM monomers and their derivatives are believed to be very helpful in resolution of inflammatory responses, and their bioactive function and mechanism have been explored in recent years. As a representative TCM monomer, Bergenia purpurascens Qi Q., et al, 2018 which is a potent compound extracted from Bergenia purpurascens, has been demonstrated to exert numerous pharmacological effects, including antibacterial, analgesic, anti-inflammatory and antitumor activities ( Fisher et al, 2017 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…TCM monomers and their derivatives are believed to be very helpful in resolution of inflammatory responses, and their bioactive function and mechanism have been explored in recent years. As a representative TCM monomer, Bergenia purpurascens Qi Q., et al, 2018 which is a potent compound extracted from Bergenia purpurascens, has been demonstrated to exert numerous pharmacological effects, including antibacterial, analgesic, anti-inflammatory and antitumor activities ( Fisher et al, 2017 ; Wu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoramide mustard, one of these compounds, binds to DNA and prevents it from replicating and then stops cancer cells from proliferating. 4,7,8 Different from other regions of the brain, the cerebellum undergoes its major developing period from the third trimester to infant stage in humans. 5 In spite of its wide usage, CTX causes a wide range of adverse effects including immunosuppression, 6 bone marrow suppression, gonadal toxicity, leucopaenia and oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…The surplus of electrons is then transferred to oxygen molecules, generating superoxide (O 2 - ), which in turn activates damaging pathways and gives rise to other ROS in a chain reaction [ 32 ]. Previous studies have shown that bergenin diminishes intracellular levels of superoxide and other ROS by increasing the activity of antioxidant enzymes, such as superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (Gpx) [ 12 , 16 , 25 , 26 ]. In this work, the antioxidant activity of bergenin was confirmed both in vitro, by the inhibition of NO production by J774 macrophages and in vivo, by the reduction of MDA and nitrite levels in neuropathic mice’s sciatic nerve and spinal cord.…”
Section: Discussionmentioning
confidence: 99%
“…Bergenin ( Figure 1 ) is a naturally occurring C-glucoside of 4-O-methylgallic acid found in many plant species. Several therapeutic applications of bergenin have been proposed in the literature, e.g., anti-ulcerative [ 10 ], hepatoprotective [ 11 , 12 ], anticancer [ 13 ], neuroprotective [ 14 , 15 ], antidiabetic [ 16 ], anti-inflammatory [ 17 , 18 , 19 , 20 , 21 , 22 ], antinociceptive [ 17 , 23 ], and antioxidant [ 12 , 16 , 24 , 25 , 26 , 27 ]. Considering that oxidative stress and neuroinflammation play key roles in the pathophysiology of DN [ 28 ], the above-mentioned properties of bergenin may contribute to the effective control of painful DN.…”
Section: Introductionmentioning
confidence: 99%